Editorial (Thematic Issue: Regulating the CNS Grand Regulator; N-methyl-D-aspartate Receptor-Mediated Neurotransmission) - Emil Tsai, Guochuan (Current Pharmaceutical Design, 2014)
N-methyl-D-aspartate receptor (NMDAR) serves for both high cortical function and fundamental CNS mechanisms. NMDAR-mediated neurotransmission is the molecular engine for CNS development and plasticity; it is also the molecular underpin of learning, memory and cognition. Due to its critical role in CNS function, either over- or under-activation of NMDAR-mediated neurotransmission contributes significantly to the development of CNS disorders. In this issue of Current Pharmaceutical Design, the authors discuss the involvement of NMDARmediated neurotransmission in a variety of CNS disorders including schizophrenia [1], cognitive deficits in schizophrenia [2, 3], depression [4], aging [5], mild cognitive impairment and Alzheimer’s dementia [6], attention deficit hyperactivity disorder [7], frontal lobe synaptic plasticity [8] as well as autism spectrum disorder [9]. NMDAR distinguish itself in two ways: first, it is both ligand-gated and voltage-dependent; second, it requires co-activation by two ligands: glutamate or aspartate and either D-serine or glycine. The experience-dependent learning originates from these two critical coincidental mechanisms. First, the activation of non-NMDA glutamate receptor will relieve the magnesium blockade and allow the opening of NMDAR channel ionophore and calcium influx. This “coincidence rdquo; mechanism between NMDA and non-NMDA receptors provides a transduction and transformation of excitatory input from multiple modalities of stimulation through non-NMDARs into the molecular machinery of NMDAR that mediates complex CNS behaviors. In this regard, NMDAR serves as a high order integrator to summate the signals from the EPSP carried by the non-NMDARs. Second, D-serine and glycine, as obligatory co-agonists, provide another dimension of dynamics in the neocortex. D-serine and the racemic enzyme converting L-serine to D-serine are enriched in the corticolimbic regions [10]. D-serine plays a key role in NMDAR activation for high order cognitive functions, while glycine’s localization is much less specific, which is also enriched in the brain stem and spinal cord other than the forebrain. There are a variety of approaches to regulate NMDAR-mediated neurotransmission; not only by the electrophysiological and molecular coincidental mechanisms mentioned above, NMDAR-mediated neurotransmission also has multiple regulatory mechanisms. As in the aminergic or GABAergic system, the regulation can happen at the level of precursor and neurotransmitter synthesis and release, or termination of action by uptake or catabolism. Parallel to the aminergic or GABAergic systems (Table 1), administration of D-serine or glycine, can activation NMDAR to improve cognitive and psychotic symptoms as tryptophan loading can facilitate the synthesis of serotonin and improves the depressive symptoms. Blocking the high efficient uptake site of glycine transporter-1 (GlyT-1) in the forebrain [11] potentiates NMDA function similar to selective serotonin uptake inhibitor’s (SSRI’s) action to raise serotonin tone. However, D-serine appears not to have a high efficient uptake site; instead, there are low affinity exchangers alanine serine cysteine transporter-1 (ASC-1) and -2 which physiological role is unclear [12]. Therefore, D-serine regulation may provide a tone that slower in time scale than the high efficient mechanism like GlyT-1. The tonicclonic coordination between D-serine and glycine can provide another dimension of complexity, and thus possibilities of regulation.The occupation of the co-agonist site is obligatory for the activation of NMDAR. However, the presence of both glycine and D-serine is not essential since both co-agonists are full agonists with strong potency. These two co-agonists not only provide redundancy for the activation of NMDAR, it also provides an unique opportunities to regulate NMDAR [13]. Although glycine and D-serine have similar potency, the anatomic specificity favors D-serine. Other than their different anatomical localization at the gross regional level, their microanatomical and physiological functions are also different; synaptic NMDAR 2A subunit-containing and extrasynaptic 2B-containing NMDARs have different co-agonists: D-serine for synaptic NMDARs and glycine for extrasynaptic NMDARs [13]. In addition, it has been found that synaptic and extrasynaptic NMDARs have opposing effects in determining the fate of neurons; the mechanisms of cell destruction or cell survival in response to the activation of NMDAR depend in part on calcium and its route of entry, and more significantly on the subunit composition and localization of the NMDARs. Overall, the synaptic NMDAR activation is involved in neuroprotection, the stimulation of extrasynaptic NMDARs, triggers cell destruction pathways and may play a key role in the neurodegeneration associated with excitotoxicity. The multi-dimensional complexity of the physiology and pathology of NMDAR can be best exampled by these two co-agonists. Although the microscopic availability of the co-agonists matches the preferential affinity of synaptic NMDARs for D-serine and extrasynaptic NMDARs for glycine, this dichotomy is not universal. For example, long-term potentiation rely on synaptic NMDARs, but both glycine and D-serine can be involved [12]. Conversely, long-term depression requires both synaptic and extrasynaptic receptors. While the initial thought that Dserine originates from astrocytes, recent evidences indicate D-serine is also neuronal in origin [10]. Neuronal D-serine is required for NMDAR-dependent, long-term potentiation at the hippocampal CA1-CA3 synapses and proper synapse formation in the cerebral cortex. However, glycine is present on both forebrain and hindbrain, for both inhibitory and excitatory neurotransmission. Based upon the prediction that enhancement of NMDA function will improve the pathological state induced by NMDAR antagonists like phencyclidine and ketamine, glycine, a full agonist, was the first to be tested in schizophrenia [14]. However, glycine has poor efficacy and requires large amount of administration (>= 60 grams/day) to have a modest effect [15]. We first proposed D-cycloserine, a partial agonist, would be a better NMDA agent than glycine due to its CNS bioavailability. We found D-cycloserine offered an inverted-U dose-response curve consistent with its partial agonist activity in a dose-finding trial of schizophrenia [16]. To facilitate higher NMDA activation, we further conducted trials with full agonists, D-serine [17] and D-alanine [18]. As we predicted, the full agonists were able to elicit a higher level of NMDA activation and clinical improvement than the partial agonist. The dose-response of NMDA activation by the treatment of full agonist was later supported by an open-label trial, indicating 60 or 120 mg/kg D-serine has better efficacy than 30 mg/kg in symptom reduction and cognitive improvement [19]. We further hypothesized that the facilitation of NMDAR activation can be achieved by blocking the reuptake of the agonist, either glycine or D-serine. However, no high affinity uptake site for D-serine has been identified, therefore we focused on the GlyT-1 which is enriched in corticolimbic region, unlike GlyT-2 which is not present in the corticolimbic region. We also predicted, the competitive antagonist will elicit a safer pharmacological profile than the noncompetitive antagonist, for the concern that the high affinity blockade of the GlyT-1 may overactivate NMDAR, particularly when extrasynaptic NMDAR that mediates toxicity is involved. In addition, strong inhibition by noncompetitive antagonism can induce endocytosis [20]. The prototype GlyT-1 inhibitor we applied, sarcosine, is a naturally occurring amino acid, discovered at high concentration in tissues including CNS. Sarcocine’s efficacy had been proved in several small scale double blind, placebo controlled studies [21-25]. Supporting the advantage of competitive vs. noncompetitive GlyT-1 antagonist, all noncompetitive antagonists had failed the development so far, including bitopertin, which gave a weak signal at the Phase II study and did not meet its endpoints of the improvement of negative symptoms in two Phase III trials [26]. Infact, bitopertin provides a inverted-U dose-response, which also discourage the therapeutic approach of noncompetitive antagonism [27]. In addition to its efficacy in the main symptom domains of schizophrenia like positive, negative and cognitive symptoms, the depressive symptoms are also improved by NMDA enhancement treatments [23]. To determine whether the antidepressant effect is primary or secondary to the improvement of other symptom domains, we has conducted both rodent behavior studies and a trial of sarcosine treatment in major depression. In which, sarcosine treatment not only elicits an antidepressant-like behavior profile in both acute and chronic stress model of depression, but also reach a much higher remission rate than a standard SSRI treatment in major depression [28]. It had been well known that magnesium infusion can quickly relieve migraine and eclampsia, likely due to its blockade of NMDAR. Given the recent findings that NMDAR antagonists can improve the symptoms of depression, the mechanistic question was raised why both NMDA enhancement and blockade can improve the symptoms of depression [4]. It is possible that both treatments share a final common target, like m-TOR or BDNF, through some unidentified intermediate mechanism. However, NMDAR agonist and antagonist have different time scales in improving the depressive symptoms; NMDAR antagonist elicits an almost immediate effect, which is much faster than agonist treatment. At the same time, the underline molecular mechanism of NMDAR antagonists is unclear given that the proposed BDNF activation and synaptogenesis will take days to weeks to develop, while ketamine’s effect is immediate. The efficacy of NMDA treatment is not limited to schizophrenia and depression. The efficacy had been shown in improving the symptoms of dementia and obsessive compulsive disorder (OCD) by sarcosine treatment [29], which is consistent with the involvement of glutamatergic neurotransmission in dementia and memory and the circuitry of OCD. NMDA neurotransmission is ubiquitous and involved in many fundamental function of CNS including psychosis, cognition, rewarding, motor, etc. Its modulation can certainly offer beneficial outcome in the symptoms involving these circuitries. In the hindsight, though NMDA-enhancement treatment is particularly relevant to schizophrenia given that the NMDAR antagonists generate “schizophrenia-like” symptoms, it is not surprising that the treatment is also beneficial for a variety of CNS disorders. While looking back the development of aminergic and GABAergic treatments, I saw the history of glutamatergic treatments, developed in the past two to three decades, could follow a similar path. All three lines of treatments can involve neurotransmitter and its precursor (chloroziapoxide, tryptophan), agonist/antagonist (L-dopa, chlopromazine), uptake blocker (imipramine, fluoxetine, bupropion), catabolism inhibitor (iproniazid, selegiline) (Table 1). In analogy to the aminergic and GABAergic treatments, I saw the missing NMDA treatment options of: first, the neurotransmitter uptake inhibition by GlyT-1 inhibitor; second, NMDAR antagonists; third, the inhibition of the D-amino acid oxidase (DAAO), which metabolize D-serine [30]. The treatment of DAAO inhibition is analogous to monoamin oxidase inhibitors (MAOI), which upregulates monoamine for CNS disorders like depression and Parkinson disease. In another word, DAAO inhibitors are similar to MAOI in raising the tone of neurotransmitter of interest, by inhibiting the catabolism enzyme. The legendary biochemist, Sir Hans Adolf Krebs discovered D-amino acid deaminase and considered the enzyme ldquo;in search of function” [31]. Almost eighty years later, the enzyme, now known as DAAO, has gained attention as a critical regulator of CNS neurotransmission. Its main substrate, D-serine is a critically important co-agonist of the NMDAR. We recently demonstrated that sodium benzoate, as a DAAO inhibitor, can substantially improve the symptoms and neurocognition of schizophrenia, presumably enhance NMDA function by raising D-serine level [32]. In mild cognitive impairment (MCI), sodium benzoate also improves the cognition and function [33]. In late 19 century, the planet Neptune was mathematically predicted before it was directly observed; working from Le Verrier's calculations, telescopic observations of Neptune was confirming afterwards. In developing the NMDA treatment for CNS disorder, we predicted DAAO inhibition could be the last missing approach in regulating the grand regulator of CNS, NMDAR-mediated neurotransmission. To search for novel DAAO inhibitors, one of the articles in this issue discuss an innovative informatics method to determine the potential activity of DAAO inhibitors in this new frontier of CNS drug development [34].
Keywords: D-amino acid oxidase